2017
DOI: 10.1016/j.radonc.2017.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram based overall survival prediction in stereotactic body radiotherapy for oligo-metastatic lung disease

Abstract: A nomogram for prediction of overall survival after stereotactic body radiotherapy (SBRT) for pulmonary metastases was developed and externally validated. This tool might be helpful for interdisciplinary discussion and evaluation of local and systemic treatment options in the oligo-metastatic setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
33
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 27 publications
7
33
2
Order By: Relevance
“…The largest multi-institutional study that treated patients of pulmonary oligometastases with SBRT reported 2-year and 5-year OS of 53% and 24%, respectively [27]. In this study, 5-year OS was 24% in the DEGRO cohort and reached 31% and 38% in the Aarhus and Torino cohorts, respectively [27]. Although treating a different subset of patients with oligometastatic disease, our results are comparable with the surgical series [3,7].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The largest multi-institutional study that treated patients of pulmonary oligometastases with SBRT reported 2-year and 5-year OS of 53% and 24%, respectively [27]. In this study, 5-year OS was 24% in the DEGRO cohort and reached 31% and 38% in the Aarhus and Torino cohorts, respectively [27]. Although treating a different subset of patients with oligometastatic disease, our results are comparable with the surgical series [3,7].…”
Section: Discussionsupporting
confidence: 66%
“…Survival achieved in our cohort of patients is particularly encouraging as the majority of patients had multiple comorbidities; more than 42% had extra-pulmonary metastases, 75% had more than one metastases, and more than half of the patients were not treated with chemotherapy before the start of SBRT. The largest multi-institutional study that treated patients of pulmonary oligometastases with SBRT reported 2-year and 5-year OS of 53% and 24%, respectively [27]. In this study, 5-year OS was 24% in the DEGRO cohort and reached 31% and 38% in the Aarhus and Torino cohorts, respectively [27].…”
Section: Discussionmentioning
confidence: 54%
“…Tanadini‐Lang et al . evaluated prognostic factors for OS and developed a nomogram aimed at predicting OS after SBRT for pulmonary metastases . According to their study, OS was influenced by the size of the pulmonary metastatic lesion, whether synchronous metastasis was present, and whether the primary lesion was controlled.…”
Section: Discussionmentioning
confidence: 99%
“…Tanadini-Lang et al evaluated prognostic factors for OS and developed a nomogram aimed at predicting OS after SBRT for pulmonary metastases. 11 According to their study, OS was influenced by the size of the pulmonary metastatic lesion, whether synchronous metastasis was present, and whether the primary lesion was controlled. Although patients with large metastatic lesions and synchronous metastases (which are considered contraindications to metastasectomy) were more prevalent in the SBRT group in our study, their OS rates were comparable to those in the surgery group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation